Ion Exchange : Theory and Practice. - Harland, C. E. (RSC paperbacks., 1994)
Ion Exchange, 2nd Edition is a totally revised and updated version of the highly popular Monograph for Teachers, first published by The Royal Society of Chemistry in 1975. It covers the practical application of ion exchange and the synthesis of organic ion exchange resins, which have spanned nearly 60 years of development since the pioneering work of Adams and Holmes in 1935. This book covers the theory, development, and application in considerable detail and describes the history of development of ion exchange materials and the advances in their utilization in industrial processes. Key appli.